2018
DOI: 10.1002/bjs.10866
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence and death in patients with breast cancer after delayed deep inferior epigastric perforator flap reconstruction

Abstract: BackgroundPostmastectomy reconstruction using a deep inferior epigastric perforator (DIEP) flap is increasingly being performed in patients with breast cancer. The procedure induces extensive tissue trauma, and it has been hypothesized that the release of growth factors, angiogenic agonists and immunomodulating factors may reactivate dormant micrometastasis. The aim of the present study was to estimate the risk of breast cancer recurrence in patients undergoing DIEP flap reconstruction compared with that in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…For the latter, the deep inferior epigastric perforator (DIEP) flap, consisting of adipose tissue and skin from the abdomen that is transposed to the mastectomy site as a free microsurgical transplant, is commonly performed [ 1 , 2 ]. While some reports observed a worse survival for patients undergoing large reconstructive procedures, assumedly releasing growth factors that may reactivate dormant tumour cells, our group found a significantly better overall survival in DIEP patients than in matched controls without any delayed breast reconstruction [ 3 ]. The current analysis aimed to identify underlying differences between the groups that could explain these observations.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…For the latter, the deep inferior epigastric perforator (DIEP) flap, consisting of adipose tissue and skin from the abdomen that is transposed to the mastectomy site as a free microsurgical transplant, is commonly performed [ 1 , 2 ]. While some reports observed a worse survival for patients undergoing large reconstructive procedures, assumedly releasing growth factors that may reactivate dormant tumour cells, our group found a significantly better overall survival in DIEP patients than in matched controls without any delayed breast reconstruction [ 3 ]. The current analysis aimed to identify underlying differences between the groups that could explain these observations.…”
Section: Introductionmentioning
confidence: 74%
“…Interaction terms were included to test for effect modification and to estimate the effect of exposure in each stratum of the modifier after investigating the main effects. Statistically significant interaction terms were tested in the 1 [3]. As shown in Table 2, the DIEP group represent a population with a higher SES, as demonstrated by a lower proportion of individuals with primary school as the highest level of education or with a low income.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…However, only 28% of the study group comprised autologous flap reconstruction, which calls this statement into question [ 11 ]. Furthermore, with mentioned hypothesis the previous described studies should have shown more recurrences in the delayed reconstruction group compared to the mastectomy alone, which they did not (Isern et al excluded) [ 13 15 ]. In addition, a study by Allawi et al did not find any association between surgery or accidental trauma and activation of dormant micro metastases leading to higher recurrence rates of breast cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we mentioned there is no statistical difference in major complications between both procedures. Therefore, this particular factor will not be important in decision-making [ 13 ]. In summary, both procedures have their advantages and limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation